2020
DOI: 10.1038/s41598-020-66599-1
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic reprogramming related to whole-chromosome instability in models for Hürthle cell carcinoma

Abstract: Hürthle cell carcinoma (Hcc) is a recurrent subtype of non-medullary thyroid cancer. Hcc is characterized by profound whole-chromosome instability (w-CIN), resulting in a near-homozygous genome (NHG), a phenomenon recently attributed to reactive oxygen species (ROS) generated during mitosis by malfunctioning mitochondria. We studied shared metabolic traits during standard and glucose-depleted cell culture in thyroid cancer cell lines (TCCLs), with or without a NHG, using quantitative analysis of extra and intr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 72 publications
1
17
0
Order By: Relevance
“…TPC1 and Nthy-ori 3-1 cells exhibited comparably normal patterns of basal and maximal OCR in response to treatment with mitochondrial complex inhibitors, while TPC1 ρ0 cells showed extremely low basal OCR and no response to treatments, confirming normal and completely abolished mitochondrial function in the parental TPC1 and TPC1 ρ0 cells, respectively. XTC.UC1 cells exhibited an intermediate pattern, that is, lower basal OCR and partial response to mitochondrial inhibitors, data consistent with Addie et al 23 , indicating the ETC in XTC.UC1 cells being partially impaired. In contrast, another group has reported a slightly different data on mitochondrial function in XTC.UC1 cells, indicating almost complete abolishment of mitochondrial function 18 .…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…TPC1 and Nthy-ori 3-1 cells exhibited comparably normal patterns of basal and maximal OCR in response to treatment with mitochondrial complex inhibitors, while TPC1 ρ0 cells showed extremely low basal OCR and no response to treatments, confirming normal and completely abolished mitochondrial function in the parental TPC1 and TPC1 ρ0 cells, respectively. XTC.UC1 cells exhibited an intermediate pattern, that is, lower basal OCR and partial response to mitochondrial inhibitors, data consistent with Addie et al 23 , indicating the ETC in XTC.UC1 cells being partially impaired. In contrast, another group has reported a slightly different data on mitochondrial function in XTC.UC1 cells, indicating almost complete abolishment of mitochondrial function 18 .…”
Section: Resultssupporting
confidence: 88%
“…Lower levels of the TCA cycle intermediates are usually replenished, and glutaminolysis is the most important anaplerotic pathway as mentioned above. αKG is used either to generate succinate and ATP/GTP from succinyl-CoA and ADP/GDP (mtSLP) 25 and then pyruvate and lactate through malate 36 (collectively called the oxidative TCA cycle) 28,37 , or to generate citrate for fatty acid synthesis (called reductive carboxylation) 38 , especially in the TCA cycle or OXPHOS-defective cancer cells or cancer cells treated with metformin (a complex I inhibitor) 23,[39][40][41] . Alternatively, glutamine is used to synthesize nucleotides 42 or glutathione 23 .…”
Section: Discussionmentioning
confidence: 99%
“…The underlying basis of chromosomal loss remains unclear, although several hypotheses have been proposed ( 48 , 49 ). Specific chromosomes appear to undergo gains or losses more frequently than others, suggesting that unique selective pressures are exerted on individual chromosomes.…”
Section: Chromosome Gains and Losses In Hccmentioning
confidence: 99%
“…ROS act as deleterious molecules that induce cellular damage in several (intra)cellular components and can act as secondary messengers. It was recently demonstrated that metabolic readjustments, and (in)balances of ROS intracellular levels, are related with genomic instability in oncocytic tumors ( 53 ). The aforementioned observations are relevant for the development of the oncocytic phenotype that were studied in the somatic context.…”
Section: Chromosomal Loss and Gains In Oncocytic Tumorsmentioning
confidence: 99%